Potential methane oxidation, production, organic matter compositon, gene copies, and environmental data - Robroek, Bjorn J. M.; Jassey, Vincent E. J.; Kox, Martine A. R.; Berendsen, Roeland L.; Mills, Robert T. E.; Cécillon, Lauric; Puissant, Jéremy; Meima–Franke, Marion; Bakker, Peter A. H. M.; Bodelier, Paul L. E. (Dryad Digital Repository, 2015)
In early June 2011, 48 experimental plots (50 × 50 cm) were established in lawn (n = 24) and hummock microhabitats (n = 24) in a Sphagnum-dominated ombrotrophic peatland in the Store Mosse National Park, Sweden (57°17’54 N, 14°00’39 E). In both microhabitats, the vascular plant functional type (PFT) composition was manipulated by removing (clipping) ericoids (–Eric), graminoids (–Gram), or both. A set of control plots remained intact. One year later, peat samples (c. 20 g. f. wt) were collected from all plots (n =48) at the aerobic/anaerobic boundary (10 – 30 cm below the peat surface, microhabitat dependent). These samples were used to measure potential methane production, potential methane oxidation, organic matter chemistry, pmoA gene copies, and environmental data.